Sharing Prosperity: Distributive Justice Framework in An Islamic Moral Economy - Ratna Mulyany; Hafas Furqani (Jurnal Madania)
The issue of distribution in an Islamic economy is not about the allocation of resources/output per se. It is about a ‘just’ allocation of resources/output. This article attempts to elaborate Islamic concept of distribution by exploring the goals of distribution in Islamic economics and mechanisms to achieve distributive justice goals. The focus of discussion is about how to realize ‘distributive justice’ in an Islamic moral economic framework by considering all dimensions: right and responsibility, effort and surplus of individual and public interest. In that spirit, the policy for distributive justice in an Islamic moral economy aims to achieve certain objectives, namely (1) fulfilment of basic needs, (2) establishing socio-economic justice and (3) economic empowerment. To achieve those objectives, Islam uses both moral exhortation to encourage voluntary action and rules/legal measures to ensure distribution/allocation of wealth in society. The distribution scheme in an Islamic economy would attempt to eliminate poverty and deprivation so that the basic needs of all are duly fulfilled. In practice, Islamic economics distribution system is done through (1) the establishment of initial conditions in distribution as the basis upon which operational distribution should be taken place during production and after production; (2) distribution through factor payment; and (3) distribution through transfer payment in the form of compulsory transfers, voluntary transfers and transfer through state.